Developing and Presenting a Shadow Leadership Model in the Ministry of Water Resources of Iraq - Khamas, Hayder Abdulrahman; Dalvi, Mohammad Reza; Muhammad Abbas, Zaki; Sadeghi, Mehrdad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to develop and present a model of shadow leadership in Iraq’s Ministry of Water Resources by examining its causal conditions, intervening factors, strategies, and consequences. Methods and Materials: The study employs a mixed-methods approach, integrating qualitative and quantitative research. In the qualitative phase, 18 experts, including university faculty members specializing in behavioral sciences and water resource professionals, were selected through purposive sampling for in-depth interviews. The qualitative data were analyzed using grounded theory, including open, axial, and selective coding. In the quantitative phase, 384 employees of the Ministry of Water Resources were surveyed using a researcher-designed questionnaire based on qualitative findings. The questionnaire’s validity was assessed using the Content Validity Ratio (CVR), and its reliability was confirmed with a Cronbach’s alpha of 0.858. Data analysis involved structural equation modeling (SEM) to test the proposed model. Findings: The results indicate that shadow leadership in Iraq’s Ministry of Water Resources is shaped by political, social, and institutional factors. Causal conditions include power challenges, shadow power requirements, social challenges, environmental instability, and governmental shortcomings. Contextual conditions such as networked power, ideological influence, and media control reinforce shadow leadership mechanisms. Intervening factors, including critics’ management, stakeholder expectations, and political identity, shape strategic actions. Identified strategies encompass social development, professional development, media transformation, and fear-based cultural tactics. The consequences highlight both stabilizing effects, such as leadership efficiency and interaction development, and challenges, such as political control and reduced transparency. Conclusion: Shadow leadership operates as an alternative mechanism of influence in bureaucratic institutions, particularly where formal leadership structures are constrained by political and governance challenges. While it can stabilize decision-making, it also poses risks to transparency and accountability. Strengthening formal governance mechanisms, fostering ethical leadership, and increasing participatory decision-making can mitigate the adverse effects of shadow leadership while leveraging its stabilizing role. Keywords: Shadow leadership, informal power structures, governance, political influence, Iraq, structural equation modeling, grounded theory.